Changes of leaf anatomical profile of cocoa clones seedlings in response to drought. - Fakhrusy Zakariyya; Didik Indradewa; Teguh Iman Santoso (Indonesian Coffee and Cocoa Research Institute, 2019)
Cocoa is a plant that is very sensitive to drought during its growth and development phase, which causes changes up to the anatomical and morphologicallevel. This research is aimed to examine the changes on several leaf anatomical characteristics of three cocoa clones under the drought stress. This research was conducted in a greenhouse of Indonesian Coffee and Cocoa Research Institute, Jember, East Java, Indonesia in January – December 2017. The research was designedusing randomized complete block design with two factors including clones and watering time interval, with three replications. The clone factor comprised of ICS 60,KW 641, and Sulawesi 1. The result showed that the clones of Sulawesi 1 and KW 641 cocoa had a higher mesophyll thickness, lower stomatal density, narrowerstomatal opening, thicker abaxial and adaxial epidermis, and higher relative water content compared to ICS 60 clone. The 8-day watering interval caused a decreasein mesophyll thickness, leaf thickness, increase in stomatal density, stomatal closure, decrease in abaxial epidermis thickness, and decrease in water status within the plant tissue. The thicker the leaf mesophyll tissue, the higher the leaf water content was. This showed that the water status within a plant leaf tissue determined bythe leaf mesophyll thickness.